2022
DOI: 10.1186/s12913-022-08090-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient navigator team perceptions on the implementation of a citywide breast cancer patient navigation protocol: a qualitative study

Abstract: Background In 2018 Translating Research Into Practice (TRIP), an evidence-based patient navigation intervention aimed at addressing breast cancer care disparities, was implemented across six Boston hospitals. This study assesses patient navigator team member perspectives regarding implementation barriers and facilitators one year post-study implementation. Methods We conducted in-depth qualitative interviews at the six sites participating in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Navigator training and the support of care team members mitigated some of these challenges. These barriers and facilitators to implementation mirror those identified in existing literature that analyzes patient navigation in non-postpartum settings such as oncology [25][26][27]. Such concordance supports the use of implementation frameworks to identify barriers and facilitators to the implementation of postpartum patient navigation.…”
Section: Discussionsupporting
confidence: 63%
“…Navigator training and the support of care team members mitigated some of these challenges. These barriers and facilitators to implementation mirror those identified in existing literature that analyzes patient navigation in non-postpartum settings such as oncology [25][26][27]. Such concordance supports the use of implementation frameworks to identify barriers and facilitators to the implementation of postpartum patient navigation.…”
Section: Discussionsupporting
confidence: 63%
“…This process used three rounds of a modified-Delphi technique, followed by cognitive interviews, and deliberations among the research team, SAB, and PAB members to identify, operationalize, and pre-test CFIR survey items. Many studies using the CFIR to implement and evaluate clinical practices rely largely on qualitative methods to identify salient constructs [34][35][36][37][38][39]. Our approach is unique in employing an interactive process that begins with examining all CFIR constructs to prospectively and quantitatively examine implementation barriers and facilitators [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of high-quality formal and informal relationships and networks, it has been found that facilitators included robust administrative support, program functioning and team cohesion 13,15 . Conversely, developments in mental health peer support programs highlighted the fact that implementation in a healthcare setting can be hampered by role confusion, inadequate training of HPs working with peers or lack of professional development, and the slow pace of development 13,14,[27][28][29][30][31][32] .…”
Section: Relational Connectionmentioning
confidence: 99%
“…To increase visibility, ongoing and repeated reminders that peer support is available through email noti cations or distribution of marketing material could be bene cial 13 . Indeed, frequent communication with HPs has shown to be helpful in peers meeting patients' needs through their discussions and in helping to successfully implement the peer support program 15,35,37 . Similarly, APs mentioned that creating opportunities to have discussions with team members is essential for ensuring their work is recognized.…”
Section: Communicationsmentioning
confidence: 99%
See 1 more Smart Citation